ปัจจัยที่มีความสัมพันธ์กับทักษะการสื่อสารเชิงสุขภาพ ของนักศึกษาหลักสูตรสาธารณสุขศาสตรบัณฑิต สาขาวิชาสาธารณสุขชุมชน คณะสาธารณสุขศาสตร์ และสหเวชศาสตร์ สถาบันพระบรมราชชนก: Factors related to Health Communication Skills of Bachelor of Public Health Students in Community Public Health Program, Faculty of Public Health and Allied Health Sciences, Praboromarajchanok Institute - สมมาตย์ เจตนิพิฐ; intakanok, Amarin (วารสารวิชาการกรมสนับสนุนบริการสุขภาพ, 2025)
การวิจัยครั้งนี้เป็นการศึกษาแบบภาคตัดขวางเชิงวิเคราะห์ มีวัตถุประสงค์เพื่อศึกษาทักษะการสื่อสาร เชิงสุขภาพและปัจจัยที่มีความสัมพันธ์กับทักษะการสื่อสารของนักศึกษาหลักสูตรสาธารณสุขศาสตรบัณฑิต สาขาวิชาสาธารณสุขชุมชน คณะสาธารณสุขศาสตร์และสหเวชศาสตร์ สถาบันพระบรมราชชนก กลุ่มตัวอย่าง คือ นักศึกษาวิทยาลัยการสาธารณสุขสิรินธร จำนวน 7 แห่ง ปีการศึกษา 2567 ชั้นปี 3 และ 4 จำนวน 357 คน สุ่มตัวอย่างโดยการสุ่มแบบหลายขั้นตอน เก็บรวบรวมข้อมูลระหว่างเดือนมกราคม - มีนาคม 2568 โดยใช้ แบบสอบถามออนไลน์ที่ผ่านการตรวจสอบคุณภาพ วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา และสถิติอนุมาน Multiple Logistic Regression นำเสนอค่า ORAdj , 95% CI และ P-value ผลการวิจัย พบว่า กลุ่มตัวอย่างส่วนใหญ่เป็นเพศหญิง ร้อยละ 84.59 อายุเฉลี่ย 21 ปี (S.D.=0.97) มีทักษะการสื่อสารเชิงสุขภาพระดับสูง คะแนนเฉลี่ย 78.85 คะแนน (S.D.=10.15) ผลการวิเคราะห์พบปัจจัยที่มีความสัมพันธ์กับทักษะการสื่อสารเชิงสุขภาพอย่างมีนัยส????ำคัญทางสถิติ ได้แก่ ปัจจัยระดับระหว่างบุคคล (ORAdj = 15.63,95% CI = 7.66-31.88, P-value <0.01) และปัจจัยระดับชุมชน (ORAdj = 4.35, 95% CI = 2.30-8.24, P-value <0.01) ผลการวิจัยครั้งนี้แสดงให้เห็นว่า การพัฒนาทักษะการสื่อสารเชิงสุขภาพของนักศึกษาควรให้ความสำคัญ กับการสร้างปฏิสัมพันธ์ระหว่างบุคคล และการพัฒนาสภาพแวดล้อมของชุมชนที่เอื้อต่อการสื่อสารเชิงสุขภาพ รวมทั้งการพัฒนาทักษะการสื่อสารเชิงสุขภาพอย่างต่อเนื่องตลอดหลักสูตร This cross-sectional analytical study aimed to determine the level of health communication skills and factors associated with these skills among undergraduate students in the Bachelor of Public Health Program, Community Public Health Major, Faculty of Public Health and Allied Health Sciences, Praboromarajchanok Institute. The study sample consisted of third and fourth-year students enrolled at seven Sirindhorn College of Public Health during the 2024 academic year, totaling 357 participants. Samples were selected using a multistage random sampling technique. Data were collected from January to March 2025 using an online questionnaire with verified quality vielding a Cronbach’s alpha coefficient of 0.98 Data were analyzed using descriptive statistics and inferential statistics, specifically multiple logistic regression, with results presented as ORAdj, 95% CI, and p-value. The results showed that the majority of participants were female (84.59%), with an average age of 21 years (S.D. = 0.97). Most of them had a high level of health communication skills, average score of 78.85 (S.D. = 10.15). Factors significantly associated with health communication skills were interpersonal-level factors (ORAdj = 15.63, 95% CI = 7.66–31.88, p-value < 0.01) and community-level factors (ORAdj = 4.35, 95% CI = 2.30–8.24, p-value < 0.01). The findings indicate that developing students’ health communication skills should focus on enhancing interpersonal interactions and fostering a community environment conducive to health communication, as well as promoting the continuous development of health communication skills throughout the curriculum.